Changes in the Phenotype of Winter Wheat Varieties Released Between 1920 and 2016 in Response to In-Furrow Fertilizer: Biomass Allocation, Yield, and Grain Protein Concentration - Maeoka, Rafael E.; Sadras, Victor O.; Ciampitti, Ignacio A.; Diaz, Dorivar R.; Fritz, Allan K.; Lollato, Romulo P. (Frontiers in Plant Science, 2020)
Plant breeding has increased the yield of winter wheat (Triticum aestivum L.) over decades, and the rate of genetic gain has been faster under high fertility in some countries. However, this response is not universal, and limited information exists on the physiological traits underlying the interaction between varieties and fertilization. Thus, our objectives were to identify the key shifts in crop phenotype in response to selection for yield and quality, and to determine whether historical and modern winter wheat varieties respond differently to in-furrow fertilizer. Factorial field experiments combined eight winter wheat varieties released between 1920 and 2016, and two fertilizer practices [control versus 112 kg ha-1 in-furrow 12 -40-0-10-1 (N-P2O5-K2O-S-Zn)] in four Kansas environments. Grain yield and grain N-removal increased non-linearly with year of release, with greater increases between 1966 and 2000. In-furrow fertilizer increased yield by 300 kg ha-1 with no variety × fertility interaction. Grain protein concentration related negatively to yield, and the residuals of this relationship were unrelated to year of release. Yield increase was associated with changes in thermal time to critical growth stages, as modern varieties had shorter vegetative period and longer grain filling period. Yield gains also derived from more kernels m-2 resultant from more kernels head-1. Historical varieties were taller, had thinner stems, and allocated more biomass to the stem than semi-dwarf varieties. Yield gains resulted from increases in harvest index and not in biomass accumulation at grain filling and maturity, as shoot biomass was similar among varieties. The allometric exponent (i.e., the slope between log of organ biomass and log of shoot biomass) for grain increased with, and for leaves was unrelated to, year of release. The ability of modern varieties to allocate more biomass to the kernels coupled to an early maturity increased grain yield and grain N-removal over time. However, increases in grain yield were greater than increases in grain N-removal, reducing grain protein concentration in modern varieties.